PERFIL NUTRICIONAL DE IDOSOS DA AREA URBANA DE IJUI, RS - BEIER, LIEGE L.; ROST, DEBORA; MACHADO, LUCIELE D. L.; TUSSET, JOSIANE; BATTISTI, IARA D. E.; SCHWEIGERT, INGRID D.; DALLEPIANE, LOIVA B.; BELLE, TANIA R. L. (Salão do Conhecimento, 2013)
Resumo